2019
DOI: 10.1016/j.landurbplan.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spending time outside on experience of nature and environmental attitudes

Abstract: Urbanization threatens biodiversity and people's opportunities to interact with nature. This progressive disconnection from the natural world is profoundly concerning as it affects human health, wellbeing, attitudes and behaviors towards nature. Increasing the quantity of experiences of nature (EoN) can enhance health and wellbeing benefits, but it remains unclear whether it can also affect environmental attitudes across different countries. Here, we conducted a cross-cultural survey among 741 people from Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 53 publications
3
38
3
2
Order By: Relevance
“…There are other important outcomes of encouraging people to visit actual natural settings of course. Living vegetation and other features provide myriad ecosystem services beyond the cultural domain that encompasses human health and well-being, such as provisioning of food and clean water (Bratman et al, 2019 ; Keeler et al, 2019 ), which can be better realized by local residents if a connection with these settings is built over repeated visitation (Richardson et al, 2016 ; Colléony et al, 2019 ; Rosa and Collado, 2019 ). Finally, ethical sensibilities could encourage the protection of the possibility for other forms of life to develop and thrive, entirely aside from their utility to humans (Leopold, 1949 ; Hartig, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are other important outcomes of encouraging people to visit actual natural settings of course. Living vegetation and other features provide myriad ecosystem services beyond the cultural domain that encompasses human health and well-being, such as provisioning of food and clean water (Bratman et al, 2019 ; Keeler et al, 2019 ), which can be better realized by local residents if a connection with these settings is built over repeated visitation (Richardson et al, 2016 ; Colléony et al, 2019 ; Rosa and Collado, 2019 ). Finally, ethical sensibilities could encourage the protection of the possibility for other forms of life to develop and thrive, entirely aside from their utility to humans (Leopold, 1949 ; Hartig, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been demonstrated that merely spending more time in nature is not enough to foster concern for the natural environment and that more conscious engagement with nature is crucial (Colléony et al. 2019). Indeed, positive correlations between species diversity, vegetation cover, and well‐being and health occur (Marselle et al.…”
Section: Introductionmentioning
confidence: 98%
“…2018; Colléony & Shwartz 2019; Colléony et al. 2019). Because people's affinity for nature plays a significant role in the way they interact with nature (e.g., Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…As urbanization continues at an alarming rate, it not only threatens biodiversity but also increasingly separates people from the natural environment [1], which is directly linked to undesirable social-related health diseases such as obesity, diabetes, depression, and mental fatigue [2,3]. During the last decade, many studies have demonstrated a positive association between nature and individuals’ health [4,5,6].…”
Section: Introductionmentioning
confidence: 99%